Bond behavior between lightweight aggregate concrete and normal weight concrete based on splitting-tensile test. (10th June 2019) - Huang, Hua; Yuan, Yujie; Zhang, Wei; Gao, Zichen
Highlight: Influences of bond properties of LWC/NWC were experimentally investigated. A crucial influence on the bond strength of LWC/NWC based on different key parameters. Significant differences existed between the experimental data and the predicted results with standards. Abstract: Lightweight concrete (LWC) is an advanced concrete with the combined advantage of being both lightweight and high-strength. LWC is an excellent option for decreasing the self-weight of a structure while offering many additional benefits such as the comprehensive utilization of resources and environmental protection by incorporating industrial solid wastes, including fly ash and silica fume. This study examined the bond properties of LWC and normal weight concrete (NWC) based on splitting-tension tests and by considering the relevant factors of LWC, such as its strength grade, interfacial agent, use of steel fibers and interface roughness. Seven concrete mixtures were tested, including six LWC mixtures, with compressive strengths between 40 and 60 MPa and a density range between 1600 and 1800 kg/m 2, and a single NWC mixture, with a compressive strength of 60 MPa. Within these mixtures, three interfacial agents, three levels of interface roughness, and a single type of steel fiber were adopted. Overall, the results indicate that all of the factors mentioned above significantly influence the bond strength between NWC and LWC. Based on the test data and various calculations relevant to NWC and LWC, certain limits are proposed that fall within accepted methods given in fib Model Code 8.